Unlocking the Power of Physical Activity in Inflammatory Bowel Disease: A Comprehensive Review - Jiajia Chen; Shaopeng Sun (Gastroenterology Research and Practice)
Summary: IBD is a chronic disease with no cure. Although medication is the main treatment modality, it requires careful consideration of its risks and benefits. PA has proven to be an effective nondrug treatment that can slow the progression of various chronic diseases and enhance patients’ quality of life. However, the correlation between PA levels and clinical outcomes of IBD remains unclear.